2021
DOI: 10.3389/fpubh.2021.543913
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Healthcare Providers About the Use of Social Media to Manage a Healthy Diet in Saudi Arabia

Abstract: Purpose: The objective of this study is to investigate the perceptions of healthcare providers about the use of social media for healthy diet management in Saudi Arabia.Participants and Methods: A cross-sectional study was designed to investigate the use of social media healthy diet management. The sample constituted 308 healthcare professionals from Saudi Arabia. The social media application, WhatsApp is employed to distribute the questionnaire, which has achieved a response rate of 50.61%. Out of the total p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Meanwhile, usage has substantially increased in Saudi Arabia, where rates are thought to be among the highest in the world [35]. In 2021, approximately 79% of the Saudi population (27.8 million) were considered active social media users, with three-quarters of these being young adults [39]. The State of Social Media in Saudi Arabia (published in 2012 and 2013) showed that the Kingdom had the highest national rankings in both YouTube video views (90 million) and Twitter usage [40].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, usage has substantially increased in Saudi Arabia, where rates are thought to be among the highest in the world [35]. In 2021, approximately 79% of the Saudi population (27.8 million) were considered active social media users, with three-quarters of these being young adults [39]. The State of Social Media in Saudi Arabia (published in 2012 and 2013) showed that the Kingdom had the highest national rankings in both YouTube video views (90 million) and Twitter usage [40].…”
Section: Discussionmentioning
confidence: 99%
“…During the lockdown restrictions, fast food advertising on social media platforms targeting all age groups, especially adults, has grown exponentially [46]. In this study, the descriptive analysis results highlighted that almost half of the participants (58.8%) agreed that social media platforms encouraged fast-food consumption through the use of FDAs.…”
Section: Fast-food Advertising On Social Media Platforms and Fdasmentioning
confidence: 74%